Environmental exposure to pharmaceuticals: A new technique for trace analysis of carbamazepine and its metabolites in human urine - Fedorova, Ganna; Ben Ari, Julius; Tadmor, Galit; Paltiel, Ora; Chefetz, Benny (Environmental pollution (Barking, Essex, 2016)
Pharmaceutically active compounds are taken up and accumulate in crops irrigated with treated wastewater. This raises the concern of chronic human exposure to pharmaceuticals via food consumption. Thus, there is a need to develop a reliable technique to detect and quantify pharmaceuticals at environmentally relevant concentrations in human biological matrices, particularly urine. In this study, we focus on carbamazepine, an antiepileptic drug and recalcitrant compound that is taken up by crops-making it an excellent model compound for this study. This paper presents a new analytical technique enabling quantification of trace concentrations of carbamazepine and its metabolites in the urine of individuals who have been environmentally exposed. Sample preparation included extraction with acetonitrile followed by clean-up through mixed-mode ion-exchange cartridges and analysis using LC/MS/MS. This technique, which was validated for a wide range of concentrations (5-2000 ng L(-1)), exhibits low limits of quantification (3.0-7.2 ng L(-1)), acceptable recovery levels (70-120%), and low relative standard deviation (<20%). Unlike currently available methods for the analysis of water or treated wastewater that require large volumes (up to 1 L), the new method uses only 10 mL of urine. Moreover, relative to available methods for carbamazepine detection in the urine of individuals who are chronically treated with this drug, the limit of quantification values with our method are six orders of magnitude lower. The newly developed method has been successfully applied for the quantification of carbamazepine and its metabolites in the urine of healthy people exposed to this pharmaceutical through their diet. Our analytical protocol can provide the scientific community and stakeholders with real data for risk assessments and the design of policies ensuring safe use of wastewater for crop irrigation.
Keywords: Carbamazepine; Chromatography, Liquid; Humans; Tandem Mass Spectrometry; Exposure; Recovery; Environmental Monitoring; vystavení vlivu životního prostředí; lidé; LC/MS/MS; Wastewater; tandemová hmotnostní spektrometrie; monitorování životního prostředí; Waste Water; Treated wastewater; chromatografie kapalinová; Water Pollutants, Chemical; Environmental Exposure; odpadní voda; karbamazepin; chemické látky znečišťující vodu